Case scenarios in pediatric and adolescent practice - Parthasarathy, A. (Professor of pediatrics); Gupta, Alok (Pediatrician) (Jaypee Brothers Medical Publishers (P) LTD, 2014)
Presented in case study format, this book provides clinicians with latest advances in field of paediatrics. Focus on clinical approach and examination techniques with emphasis on diagnostic tools. Each topic includes key learning points.